The role of social accountable medical education in addressing health inequity in Aotearoa New Zealand. (29th November 2019) - Pitama, Suzanne; Beckert, Lutz; Huria, Tania; Palmer, Suetonia; Melbourne-Wilcox, Maia; Patu, Maira; Lacey, Cameron; Wilkinson, Tim J.
ABSTRACT: Medical education provides a locus to apply the principles of social justice to advocate for indigenous health inequities. Within the education field, social accountability measures have been used to increase equity. This study uses a social accountability lens to explore the perspectives and experiences of academic and clinical leaders, students, and patients engaged with the Hauora Māori curriculum at the University of Otago Christchurch. Using Kaupapa Māori research as a theoretical framework, and drawing on qualitative analysis, three themes were identified; horopaki/contexts, mihini/mechanisms and tukunga iho/outcomes. These three themes described the activities, enablers and mechanisms that identified the Hauora Māori curriculum as a method for achieving social accountability among Māori communities, medical education, and health services.